Narrative Works in History - Munslow, Alun (Narrative Works, 2016)
The past is the time before now and history is the narrative historians create about it. The key question, then, is how does narrative work in turning the past into a history? It is unavoidable that only through their history narratives can the historians elucidate a meaning and explanation for the past. While empiricism (stating what actually happened) and analysis (the inference of probable meaning) are two foundations for “doing history,” the third is the creation of a narrative to deliver the historians’ judgments. What this means is that “the history narrative” is the only mechanism available for creating explanation and meaning. So, how does the history narrative create history?